2020
DOI: 10.1007/s40801-020-00217-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Cost and Utilization Associated with Biologic Treatment Patterns Among Patients with Psoriatic Arthritis: Analyses from a Large US Claims Database

Abstract: Background Costs associated with biologic switching and discontinuation can be high in psoriatic arthritis (PsA), and their inappropriate use may have cost implications for patients, healthcare professionals, and payers. Objective To compare direct costs of treatment switchers, non-switchers, and discontinuers among patients with PsA who newly initiated a biologic. Methods Patients with PsA aged ≥ 18 years with ≥ 1 pharmacy claim for an FDA-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Our findings are also consistent with a number of studies [11][12][13][27][28][29][30][31][32][33][34][35][36][37][38] conducted in varying settings, which have assessed health care costs associated with non-persistence in treatment with biologics in IA indications. While most of them evaluated costs only in RA, a few studies considered other IA indications either additionally [12] or exclusively [33,37]. Apart from the costs of the biologic therapies, persistence with biologics was consistently reported to be associated with cost offsets in HCRU compared to non-persistence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are also consistent with a number of studies [11][12][13][27][28][29][30][31][32][33][34][35][36][37][38] conducted in varying settings, which have assessed health care costs associated with non-persistence in treatment with biologics in IA indications. While most of them evaluated costs only in RA, a few studies considered other IA indications either additionally [12] or exclusively [33,37]. Apart from the costs of the biologic therapies, persistence with biologics was consistently reported to be associated with cost offsets in HCRU compared to non-persistence.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to costs of HCRU, Ziegelbauer and colleagues [13] found that non-persistence with SC-TNFis was associated with higher indirect costs in treatment for IA in a cohort of German patients. However, both that German study [13] and the most the other studies investigating this matter [11,12,28,[31][32][33][34][35][36][37][38] have evaluated costs associated with non-persistence using claims data, which due to selection bias may limit the generalizability to the general IA population. Our study utilizes population-based registers with good coverage, thus allowing for increased generalizability of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, many different systemic therapy options are available nowadays to treat psoriasis ( 12 , 13 ). Modern biologics have been shown to be highly effective; however, these medications are expensive and can place a high financial burden on the healthcare system, if frequently and irrationally prescribed ( 14 , 15 ). Fumaric acid esters (FAEs) remain an appropriate and much more cost-effective therapy option for patients with moderate to severe psoriasis ( 12 ).…”
mentioning
confidence: 99%